Pharmacodynamic Properties of Long Lasting Butyryl Heparin Derivatives in the Rabbit - Saivin, S; Caranobe, C; Petitou, M; Lormeau, J C; Houin, G; Boneu, B (Thrombosis and Haemostasis, 1992)
This paper reports on the pharmacodynamic properties of butyryl derivatives of unfractionated heparin (C4-UH) and of low molecular weight heparin (C4-CY 216) after bolus intravenous injection, constant infusion and subcutaneous administration to rabbits. The pharmacodynamic properties of the two butyryl derivatives were compared to those of the parent compounds, unfractionated heparin (UH) and low molecular weight heparin (CY 216). After bolus intravenous injection of increasing doses, the disposition of the butyryl derivatives were comparable to that of their parent compounds up to 3 mg kg-1. Over this dose, their clearances became 2 to 3 times lower. These long lasting properties were confirmed by constant intravenous infusion experiments. After subcutaneous administration, the bioavailability of C4-UH remained low (10%) at any dose while that of C4-CY 216 ranged from 42 to 120%. If these findings are confirmed in man, these new derivatives open the possibility of treating established deep vein thrombosis with only one daily injection of a butyryl derivative of low molecular weight heparin.